2008
DOI: 10.1007/s00221-008-1666-4
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral deficits in fine motor control and pinch grip force in patients with unilateral carpal tunnel syndrome

Abstract: Subjects with carpal tunnel syndrome (CTS) typically describe self-perceived pinch grip deficits, clumsiness sensations and difficulty with grasping small objects, which suggest the existence of a fine motor control deficit. No previous studies have investigated fine motor control and pinch grip force bilaterally in patients diagnosed with moderate CTS. Our aim was to investigate differences in fine motor control ability and pinch grip force between patients with unilateral CTS and healthy controls. Subtests o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…These results are similar to those previously reported for individuals with chronic whiplash 57,59 and unilateral migraine. 29 In addition, the results of the current study are consistent with those…”
Section: Pressure Pain Sensitivitysupporting
confidence: 91%
See 1 more Smart Citation
“…These results are similar to those previously reported for individuals with chronic whiplash 57,59 and unilateral migraine. 29 In addition, the results of the current study are consistent with those…”
Section: Pressure Pain Sensitivitysupporting
confidence: 91%
“…70 Several studies have demonstrated that LE is characterized by bilateral sensory 21,22,53 and motor 6,54 changes, suggesting central sensitization mechanisms. Furthermore, vibration, 63 thermal, 19 and motor 29 impairments have been identified bilaterally in patients with unilateral CTS, which also suggests the presence of central mechanisms. A recent study demonstrated that LE is different to CTS in some sensory disturbances, as no deficit in thermal and vibration detection thresholds were found in individuals with LE.…”
Section: Participants P Atients Diagnosed With Cts Bymentioning
confidence: 84%
“…Rheumatoid arthritis, 8 osteoarthritis, 9 carpal tunnel disease 10 and stroke 11 have all been reported as having lower finger strengths. In addition to neurological disease causing lower strengths these can also cause deficits in control and direction of force application, 11 which are also required to co-ordinate functional tasks such as squeezing a bottle.…”
mentioning
confidence: 99%
“…For instance, it has been reported that women with unilateral moderate CTS exhibit bilateral deficits in fine motor control and pinch tip grip force compared to healthy women. 19 In fact, these deficits seem to be similar in individuals with minimal, moderate, or severe CTS. 15 Deficiencies in sensory and motor processes often result in alteration in force adaptations, which can lead to the inability to adequately perform functional activities with the upper limb.…”
mentioning
confidence: 94%
“…The patients were asked to watch the screen for visual feedback. 15,19 They performed the pinch with the thumb below and either the index or little finger on top of the pinch grip dynamometer. The mean of 3 trials with each finger was calculated and used for the analysis.…”
Section: Physical Outcomesmentioning
confidence: 99%